2002
DOI: 10.1016/s0022-5347(05)65174-9
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study: Watchful Waiting For Localized Low To Intermediate Grade Prostate Carcinoma With Selective Delayed Intervention Based On Prostate Specific Antigen, Histological And/Or Clinical Progression

Abstract: A policy of watchful waiting with selectively delayed intervention based on predefined criteria of disease progression is feasible. This strategy offers the benefit of an individualized approach based on the demonstrated risk of clinical or biochemical progression with time and, thus, it may decrease the burden of therapy in patients with indolent disease, while providing definitive therapy for those with biologically active disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
194
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(204 citation statements)
references
References 17 publications
4
194
0
3
Order By: Relevance
“…Active surveillance, first described by Choo et al, 3,4 is an approach to the management of localised prostate cancer that aims to avoid overtreatment of men with indolent cancers, whereas still providing treatment with radical intent within a window of curability for those who need it. 5 In contrast to traditional watchful waiting, a policy of observation with the use of palliative treatment for symptomatic progression, active surveillance consists of close monitoring with radical treatment recommended on the basis of prostate-specific antigen (PSA) kinetics or the detection of adverse histology in repeat biopsies.…”
Section: Introductionmentioning
confidence: 99%
“…Active surveillance, first described by Choo et al, 3,4 is an approach to the management of localised prostate cancer that aims to avoid overtreatment of men with indolent cancers, whereas still providing treatment with radical intent within a window of curability for those who need it. 5 In contrast to traditional watchful waiting, a policy of observation with the use of palliative treatment for symptomatic progression, active surveillance consists of close monitoring with radical treatment recommended on the basis of prostate-specific antigen (PSA) kinetics or the detection of adverse histology in repeat biopsies.…”
Section: Introductionmentioning
confidence: 99%
“…Indications for treatment were PSA progression, defined as a PSADT o2 y; histologic progression, defined as upgrading to Gleason score Z8 on rebiopsy; or clinical progression. By the time of the latest update, 15 206 men had entered the study. They ranged in age from 49 to 84 y with a median of 70 y.…”
Section: Initial Results Of Active Surveillancementioning
confidence: 99%
“…There is no consensus on the selection criteria used to identify patients for surveillance. [15][16][17] My own policy is to offer active surveillance as an option to men who have clinical stage T1/2 disease, a primary Gleason grade of r3, with r50% of biopsy cores involved and a PSA level of o15 ng/ml. Initial analyses have shown that the variation in the findings between initial and repeat biopsies, at least within the first few years of surveillance, reflect the limitations of sampling, rather than tumour evolution.…”
Section: Initial Results Of Active Surveillancementioning
confidence: 99%
“…Some guidelines have been developed to evaluate men on watchful waiting protocols. 10 A recent study provides evidence that in clinically localized prostate cancer, radical prostatectomy may reduce the cancer-specific but not the overall mortality compared to watchful waiting. 2 At first glance, the debate regarding treatment seems easier in locally advanced disease, as it is known that patients with node positive disease, receiving no therapy will die due to prostate cancer within a short period of time.…”
Section: Discussionmentioning
confidence: 99%